RESPONSE OF MAIZE TO DIFFERENT NITROGEN SOURCES AND TILLAGE SYSTEMS UNDER HUMID SUBTROPICAL CONDITIONS - K. Shahzad; A. Khan; J. Smith; M. Saeed; S.A. Khan (Journal of Animal and Plant Sciences, 2015)
Tillage systems (minimum, conventional and deep) with different sources of nitrogen (bioslurry, poultry manure and chemical fertilizer) were studied through field experiments at Gujjar Seed and Nursery Farm, Haripur, Khyber-Pakhtunkhwa, Pakistan, for two consecutive years (2012-2013) in a randomized-complete-block-design with split plots and four replicates. The tillage systems were kept in main plots while nitrogen treatments with different combinations of chemical fertilizer, poultry manure and bioslurry were distributed in sub-plots. The results showed that deep tillage with 100% chemical fertilizer (135 kg N ha-1) produced maximum plant height, stem diameter, cob length, cob diameter and number of grain rows per cob. However, deep tillage with combined application of 50% chemical fertilizer (67.5  kg N ha-1), 25% poultry manure (1.9  t ha-1) and 25% bioslurry (2.1 t ha-1) produced maximum 1000 grain weight, biological yield, grain yield, plant nitrogen, phosphorous and potassium concentrations in maize shoot, and seed protein contents compared to other treatments. It is concluded that integrated use of bioslurry and poultry manure with a reduced rate of chemical fertilizer can improve maize productivity and reduce cost of chemical fertilizers. The results also suggest that, in this soil and climate, deep tillage is needed to maximise yield potential.
Keywords: bioslurry; poultry manure; maize productivity; tillage systems; humid subtropical conditions